SIMILARITIES AND DIFFERENCES CATEGORY OF CASES IN NOUN IN ENGLISH AND UZBEK LANGUAGES - Tursunov Mukhammadayubkhon; Aziz Mukhamadiev (Лучшие интеллектуальные исследования, 2024)
Annotation: This article compares and contrasts the category of cases in nouns between the English and Uzbek languages. It explores the grammatical structures and functions of cases in both languages, highlighting similarities and differences. The study aims to provide a better understanding of how nouns are inflected to indicate various grammatical relationships in English and Uzbek, shedding light on the unique features of each language's case system.